RNA Interference Inhibits DUX4-induced Muscle Toxicity In Vivo: Implications for a Targeted FSHD Therapy - Wallace, Lindsay M (Nature Publishing Group, 2012)
No treatment exists for facioscapulohumeral muscular dystrophy (FSHD), one of the most common inherited muscle diseases. Although FSHD can be debilitating, little effort has been made to develop targeted therapies. This lack of focus on targeted FSHD therapy perpetuated because the genes and pathways involved in the disorder were not understood. Now, more than 2 decades after efforts to decipher the root cause of FSHD began, this barrier to translation is finally lowering. Specifically, several recent studies support an FSHD pathogenesis model involving overexpression of the myopathic DUX4 gene. DUX4 inhibition has therefore emerged as a promising therapeutic strategy for FSHD. In this study, we tested a preclinical RNA interference (RNAi)-based DUX4 gene silencing approach as a prospective treatment for FSHD. We found that adeno-associated viral (AAV) vector-delivered therapeutic microRNAs corrected DUX4-associated myopathy in mouse muscle. These results provide proof-of-principle for RNAi therapy of FSHD through DUX4 inhibition.